Censurae Librorum - The Cup of Songs or the Universe of Sympotic Poetry - Węcowski, Marek (Polskie Towarzystwo Filologiczne, 2019)
Recenzja pracy: Vanessa Cazzato, Dirk Obbink, Enrico Emanuele Prodi (eds.), The Cup of Song. Studies on Poetry and the Symposion, Oxford: Oxford University Press, 2016, XVII, 329 pp., ISBN 978-0-19-968768-8, £88.001.